Low-income Household’s Public-rented Flats Preferences in Semarang City Using Conjoint Analysis - Winda Hanifah (Ruang, 2023)
This study aims to determine public flats preferences of low-income household respondents using conjoint analysis, so that it can be identified the relative importance of flats attributes and the utilities’s value of attribute levels that affect respondent’s choice. Survey was conducted on 35 squatter’s respondents who live in the Banjir Kanal Timur Semarang Riverbanks and 86 respondents who already dwelled in Kudu and Pondok Boro public rental flats provided by the Semarang City Government. The attributes identified to describe public flats are: rental prices, accessibility and location, facilities, and ownership rights. The study show that “rental prices” and “accessibility and location” is the most important attribute in choosing the public rental flats to live in, while “facilities” was the least important. The choice behavioral models based on age, education levels, types of job, monthly income, and family size show that respondents have different preferences based on their socio-economic characteristic.